“ANALISIS PESAN DAKWAH DALAM RUBRIK KAJIAN AL QUR’AN PADA PADA MAJALAH UMMI DALAM MENINGKATKAN PEMAHAMAN AGAMA PEMBACA”. - Wa Ode Sitti Khamaria (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT Problem in this paper is, that is how the propaganda message on study sections of the Al Qur'an in the magazine Ummi and whether the missionary message in the column in the magazine study the Al Qur'an can neither improve the understanding of readers. The purpose of this study was to determine the missionary message within the rubric of the Al Qur'an and study to find out whether the missionary message that can enhance the understanding of its readers or not The theory used in this research is the analysis of the contents of the opinion theory Holsti (1969 ).Types this study is a qualitative research method consists of analyzing the content and descriptive qualitative analysis. Data collection techniques in this study is the observation , documentation , and interviews . The results of this study is on the content of propaganda messages within the rubric of the Al Qur'an is about the study of human fitra in this world to get the light of God and how to get the light to get closer to the holy places, mosques. Allah encourages us, when entering the mosque, then leave the things of the world , because the mosques are places of worship and remembrance of Him. Allah will not accept deeds of unbelievers until they believe. Based on interviews, messages of propaganda within the rubric of the Al Qur'an study could improve the understanding of religious readers. Keywords : Message Propagation Rubric Magazine Studies at Ummi Al Qur'an.